The Laws in Medical Futility: A Comparative Study between the Malaysian, English, American, Indonesian, and Islamic Law - Baharudin, Syaheera Aina (Indonesian Comparative Law Review, 2020)
Medical futility has always been a huge blow to the medical world. While medical practitioners live to save others’ lives, some cases may not be as kind to their honorable intentions. The problems that were posed by medical futility had always spark issues of morality, ethics and laws. The paper aims to address the laws governing any medical practitioner’s actions towards medical futility which is likely to result in the death of the patient. It will look into the current laws of four nations namely Malaysia, England, the United States of America and Indonesia, with special consideration towards Islamic Jurisprudence by referring to the opinions of various scholars and jurists. This paper has come into being through the studies of many literary articles, law cases, analyzing related statutes and studying the common practices of the previously stated nations. The paper had reached some fundamental outcomes which are: Malaysia and its mother land England shares similar practice in which withholding and withdrawal of treatment is considered lawful when faced with medical futility. As for the United States of America, some states adopted laws regulating end-of-life decisions, providing guidelines and proper sanctions for non-compliance which is contrary to Indonesia which do not have a specific regulation in dealing with medical futility cases. From the Islamic law perspective, scholars had advised that heavy consideration should be given according to the Maqasid Syariah by adhering to the hierarchy of fiqh of looking after necessities, then needs, and then embellishments.